The radical Isaac : I.L. Peretz and the rise of Jewish socialism - Mahalel, Adi (State University of New York Press, 2023)
Examines the Yiddish-Hebrew writer I. L. Peretz's alignment with the Jewish working-class in Eastern Europe and his devotion to progressive politics.
Keywords: Peretz, Isaac Leib, -- 1851 or 1852-1915 -- Criticism and interpretation.; Peretz, Isaac Leib, -- 1851 or 1852-1915 -- Political and social views.; Peretz, Isaac Leib, -- 1851 or 1852-1915; BIOGRAPHY & AUTOBIOGRAPHY / Jewish.; Political and social views; Literary criticism; Criticism, interpretation, etc.; Literary criticism.; Critiques littéraires.